Microfluidic reactor geometries for radiolysis reduction in radiopharmaceuticals - Rensch, Christian Friedrich Peter; Wängler, Björn (Applied radiation and isotopes, 2012)
Autoradiolysis describes the degradation of radioactively labeled compounds due to the activity of the labeled compounds themselves. It scales with activity concentration and is of importance for high activity and microfluidic PET tracer synthesis. This study shows that microfluidic devices can be shaped to reduce autoradiolysis by geometric exclusion of positron interaction. A model is developed and confirmed by demonstrating in-capillary storage of non-stabilized [18F]FDG (2-[18F]Fluoro-2-deoxy-d-glucose) at max. 23GBq/ml while maintaining >90% radiochemical purity over 14h.